Indigenization of Instructional Materials in Speech and Stage Arts for Teacher Preparation Program - Parallag, Maricel (International Journal of Arts, Sciences and Education, 2022)
Instructional materials are powerful tools to bring about effective teaching and learning. Thus, this study aimed to develop indigenized instructional materials for Speech and Stage Arts language course. Through the collection, documentation, and transcription of speech samples and stage arts pieces from the Indigenous People and the realignment of learning competencies based on the course guide, indigenized lesson models were developed. Results show that there are speech samples and stage arts pieces available from the Gaddang and Yogad Indigenous People.; for the Gaddang, there are two (2) songs: Natalofu (It Bloomed), Ope Manque Wayi (Where is my brother and sister), story: Gakit festival and three (3) rituals: Marriage, Rites of Passage, and Healing while from the Yogad there are ten (5) songs: Wara Lubo Ku ( I had a Balloon), Yu Tuddan ( The advice), Yu Lappao ( The flower), Yu Tamba ( The Promise), Anac (Child), and two (2) rituals: Marriage rituals and rituals relating to sickness and four (4) stories: Capitan Tercero, the Yogad hero, Echague, the Yogad Homeland, and Bacao Festival. The collected, documented and transcribed pieces were used as instructional materials by integrating the selected lessons in Speech and Stage Arts. Lesson exemplars were developed by realigning Speech and Stage Arts competencies, Philippine Professional Standard for Teachers domain and competencies, and the collected speech samples from the Yogad and Gaddang Indigenous groups.